Infectious and Non-Infectious Diseases Burden Among Haitian Immigrants in Chile: A Cross-Sectional Study - Zamora-Vargas, F (Nature Research, 2020)
Chile has become a popular destination for migrants from South America and the Caribbean (low- and middle-income countries migration). Close to 200.000 Haitian migrants have arrived in Chile. Infectious and non-infectious disease burden among the Haitian adult population living in Chile is unknown. This study aimed to acquire the basic health information (selected transmissible and non-transmissible conditions) of the Haitian adult population living in Chile. A cross-sectional survey was performed, inviting Haitian-born residents in Chile older than 18 years old. Common conditions and risk factors for disease were assessed, as well as selected transmissible conditions (HIV, HBV, and HCV). 498 participants (60.4% female) from 10 communities in two regions of Chile were surveyed. Most subjects had never smoked (91.5%), and 80% drank less than one alcohol unit per month. The mean BMI was 25.6, with 45% of participants having a normal BMI (20–25). Hypertension was present in 31.5% (33% in the 25–44 age group). Prevalence of HIV was 2.4% (95 CI 1.3–4.2%), hepatitis B (HBsAg positive) was 3.4% (95 CI 2.1–5.5%), and hepatitis C was 0% (95 CI 0.0–0.9%). Quality of life showed a significant prevalence of depression and anxiety markers, particularly in those arriving in Chile less than 1 year ago. Low prevalence of obesity, diabetes, smoking, and drinking and estimated cardiovascular risk were found. Nonetheless, hypertension at a younger age, disproportionately higher prevalence of HIV and HBV infection and frequent markers of anxiety and depression were also found. Public policies for detecting and treating hypertension, HIV, and HBV screening, offering HBV vaccination, and organizing mental health programs for Haitian immigrants, are urgently needed. © 2020, The Author(s).